2005
DOI: 10.1080/00268970500052270
|View full text |Cite
|
Sign up to set email alerts
|

Infrared spectroscopy of mass-selected neutral molecular systems without chromophore: the formamide monomer and dimer

Abstract: The paper presents IR spectroscopic data and theoretical frequency calculations, in the C-H and N-H stretch region, on jet-cooled formamide molecules and dimers. By using dipolebound or quadrupole-bound anion formation, one is able to monitor IR absorption in the neutral beam on mass-selected species. For isolated formamide, resonant IR excitation leads to autodetachment of the excess electron in the dipole-bound anion. For the formamide dimer, the IR spectrum is characteristic from the cyclic dimer, with two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 20 publications
0
23
1
Order By: Relevance
“…It is characterized by some specific properties like the coplanarity of the groups attached to the nitrogen atom, a high rotational barrier and kinetic stability toward nucleophilic attack or hydrolysis. 8,9 The formamide dimer has been studied extensively by theoretical [10][11][12][13][14][15][16][17][18][19][20][21][22][23] and experimental [24][25][26] methods. The double proton transfer in the formamide dimer occurs concertedly both in the gas phase and in solution.…”
Section: Introductionmentioning
confidence: 99%
“…It is characterized by some specific properties like the coplanarity of the groups attached to the nitrogen atom, a high rotational barrier and kinetic stability toward nucleophilic attack or hydrolysis. 8,9 The formamide dimer has been studied extensively by theoretical [10][11][12][13][14][15][16][17][18][19][20][21][22][23] and experimental [24][25][26] methods. The double proton transfer in the formamide dimer occurs concertedly both in the gas phase and in solution.…”
Section: Introductionmentioning
confidence: 99%
“…Three-dimensional network arrangements similar to those in condensed phases are not appropriate for the clusters because these make a large number of dangling NH groups free from hydrogen bonding for a finite size of aggregation. A great abundance of the antiparallel dimer in a supersonic jet has been revealed by infrared absorption spectroscopy. , The ladder-like arrangements of the dimer units are the most efficient to gain a number of hydrogen bonds, minimizing dangling NH groups to 2 at both the ladder ends. Figure shows the structures optimized with the B3LYP/6-311++G(d,p) level calculations for neutral AA clusters of n = 5 and 6.…”
Section: Resultsmentioning
confidence: 99%
“…A great abundance of the antiparallel dimer in a supersonic jet has been revealed by infrared absorption spectroscopy. 31,32 The ladder-like arrangements of the dimer units are the most efficient to gain a number of hydrogen bonds, minimizing dangling NH groups to 2 at both the ladder ends. Figure 3 shows the structures optimized with the B3LYP/ 6-311++G(d,p) level calculations for neutral AA clusters of n = 5 and 6.…”
mentioning
confidence: 99%
“…While spectroscopic investigations for protonated cluster cations 86,87 and cluster anions 88 of FA have extensively been carried out, neutral clusters of FA have undergone only few spectroscopic investigations. 89,90 Because FA has no UV chromophore, FA is a typical example which the conventional IR-UV double resonance spectroscopy is inapplicable to. Successful observations of the IR spectra of FA-H 2 O and (FA) 2 have been uniquely reported by Schermann and coworkers through a development of IR dissociation/electron detachment spectroscopy based on their Rydberg electron transfer (RET) technique.…”
Section: Ii-2 Infrared Spectroscopy Of Formamide-(h 2 O) N N = 1-4 C...mentioning
confidence: 99%
“…Successful observations of the IR spectra of FA-H 2 O and (FA) 2 have been uniquely reported by Schermann and coworkers through a development of IR dissociation/electron detachment spectroscopy based on their Rydberg electron transfer (RET) technique. 89,90 Systematic and size-selective spectroscopic studies for FA-(H 2 O) n , n 41, however, have never been reported. VUV-ID-IRPDS is developed for vibrational spectroscopies of such neutral clusters without a UV chromophore, 49 and its application to FA-(H 2 O) n , n = 1-4, well demonstrates the potential of this new method.…”
Section: Ii-2 Infrared Spectroscopy Of Formamide-(h 2 O) N N = 1-4 C...mentioning
confidence: 99%